Análise sociolingüística do processo de elisão da vogal A no dialeto pessoense. - Machado, Rafaela Veloso (2008)
This current work investigates the elision‟s sociolinguistic behavior upon the João Pessoa native dialect. Elision is one of sandhi‟s extern vocalic phenomenon observed through all languages and it means fading the low vowel /a/ when it is followed by a different vowel. (ex.: menina humilde> meninumilde). This process analyses is through the theorical-methodological scope that the Quantitative Sociolinguistics comprehends. On the construction of this work it has been used a corpus of spoken language that integrates the Projeto de Variação Lingüística do Estado da Paraíba VALPB (Linguistic Variation Project of Paraíba State), composed by eighteen informers, divided by sex (masculine and feminine), age range (teenagers, adults, elders) and academic time spent (none, five to eight years and more than eleven years). The results found show that the linguistic constraints sise of the first word from a sentence, stress, prosodic constituents, vowel‟s quality present themselves as the most relevant on the elision appliance, therefore, reveling themselves as a process without great social determinants.